How to retire happy the 12 most important decisions you must make before you retire - Hinden, Stan (McGraw Hill-Ascent Audio, 2013)
The Washington Post and New York Times Business Bestseller "Everyone in the workforce today should read this book!"--HORACE B. DEETS, FORMER EXECUTIVE DIRECTOR, AARP "Want excellent insights on retirement planning from a professional who's actually experienced retirement himself? You'll get just that from Stan Hinden's book." -STEVE VERNON, COLUMNIST "Provides the most important information you'll need before and during your retirement." -MICHELLE SINGLETARY, THE WASHINGTON POST Award-winning Washington Post retirement columnist Stan Hinden's bestselling How to Retire Happy, Fourth Edition, helps you make the right decisions to ensure a happy, healthful retirement. It delivers all the expert advice you need in an easy-to-understand step-by-step style. How to Retire Happy includes everything that has made previous editions the go-to guides for retirees and near-retirees, plus: Brand-new material on health insurance and the prescription drug plan The facts about Medicare Part A (hospital), Part B (tests, doctors, preventive care), and Part D (prescription drugs) The author's personal experiences with the realities of long-term Alzheimer's care Fully updated material on Social Security strategies How to handle the financial realities of the post-meltdown economy New resources you can turn to for extra advice
Online resource; title from title details screen (O'Reilly, viewed September 27, 2022)
Keywords: Retirement -- Planning -- United States; Retirement income -- United States; Retirement -- Economic aspects -- United States; Retraite; États-Unis; Planification; Revenu de retraite; États-Unis; Retirement; Economic aspects; Retirement income; Retirement; Planning; United States; Downloadable audio books; Audiobooks; Livres audio